Right Atrial and Massive Pulmonary Artery Mechanical Thrombectomy Under Echocardiography Guidance Using the FlowTriever System. (2019) - Nezami, Nariman; Latich, Igor; Murali, Nikitha; Ali, Rahmat; Lin, Ben A.; ShervinRad, Mohammadreza; Pollak, Jeffrey; Mojibian, Hamid
Abstract : Introduction: Management of clot in transit in patients with pulmonary embolism, who are candidates for percutaneous intervention, can be challenging. This is a case report of simultaneous right atrial mechanical thrombectomy under echocardiography guidance and pulmonary artery embolectomy under fluoroscopy guidance, using the recently introduced FlowTriever system (Inari Medical Inc., Irvine, CA, USA). Report: An 88 year old female, resuscitated from cardiopulmonary arrest near the end of a total right hip arthroplasty, presented for management of suspected massive pulmonary embolism. Her right atrial thrombus was removed under transthoracic echocardiography guidance, and her pulmonary arterial thrombus was subsequently successfully treated under fluoroscopy. Discussion: The FlowTriever system can be safely and effectively used under real time transthoracic echocardiography guidance to retrieve clot in transit from the cardiac chambers, in addition to its standard application for the pulmonary artery under fluoroscopy guidance. Highlights: FlowTriever system is recently cleared by FDA for mechanical thrombectomy of pulmonary embolism. This is the first case of mechanical thrombectomy in the right atrium or ventricle under echocardiography guidance. The mechanical thrombectomy in the right atrium/ventricle was safe and resolved the patient's symptoms.